Study of an Elliptic Partial Differential Equation Modeling the Ocean Flow in Arctic Gyres - Susanna V. Haziot (Faculty of Mathematics, University of Vienna) (Journal of Mathematical Fluid Mechanics, 2021)
The abstract is available here: https://uscholar.univie.ac.at/o:1536429 The abstract is available here: https://uscholar.univie.ac.at/o:1536429